2022
DOI: 10.3390/pathogens11091020
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Analyses of New Cinnamid and Rosmarinic Acid-Derived Compounds Biosynthesized in Escherichia coli as Leishmania amazonensis Arginase Inhibitors

Abstract: Arginase is a metalloenzyme that plays a central role in Leishmania infections. Previously, rosmarinic and caffeic acids were described as antileishmanial agents and as Leishmania amazonensis arginase inhibitors. Here, we describe the inhibition of arginase in L. amazonensis by rosmarinic acid analogs (1–7) and new caffeic acid-derived amides (8–10). Caffeic acid esters and amides were produced by means of an engineered synthesis in E. coli and tested against L. amazonensis arginase. New amides (8–10) were bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Py-CoMFA (3D-QSAR) models were constructed with 34 inhibitors reported in the literature between 2018 and 2023 against arginase from L. (L) amazonensis ( La ARG). These 34 inhibitors belong to the chemical classes of chromones ( 1a–1d ) 43 , pyrazolo-pyrimidines ( 2a – 2f ) 44 , phenylhydrazines or phenylamide ( 3a – 3f ) 45 , cinnamides (cinnamic acid amides or cinnamides) ( 4a – 4k ) 4 , and esters ( 5a–5f ) 46 derived from 3,4-dihydroxycinnamic acid (caffeic acid) 47 ( 6 ) (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Py-CoMFA (3D-QSAR) models were constructed with 34 inhibitors reported in the literature between 2018 and 2023 against arginase from L. (L) amazonensis ( La ARG). These 34 inhibitors belong to the chemical classes of chromones ( 1a–1d ) 43 , pyrazolo-pyrimidines ( 2a – 2f ) 44 , phenylhydrazines or phenylamide ( 3a – 3f ) 45 , cinnamides (cinnamic acid amides or cinnamides) ( 4a – 4k ) 4 , and esters ( 5a–5f ) 46 derived from 3,4-dihydroxycinnamic acid (caffeic acid) 47 ( 6 ) (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies on this derivative, indicated the establishment of hydrophobic and polar interactions with key residues within the binding site of the enzyme, together with a metal coordination bond with the metal ions, thus supporting its micromolar inhibition of LaARG. 98 As chalcone-based compounds demonstrated to display inhibitory effects against trypanosomatids, including Trypanosoma cruzi and Leishmania spp., a series of thirty-six chalcone derivatives was evaluated in vitro on LiARG. Seven compounds exhibited LiARG inhibition above 50% at 100 μM concentration.…”
Section: Arginase Inhibitors In Leishmaniasismentioning
confidence: 99%
“…The inhibition mechanism was investigated through enzyme kinetics, and notably, one compound ( 54 ) resulted in a competitive inhibitor. Computational studies on this derivative, indicated the establishment of hydrophobic and polar interactions with key residues within the binding site of the enzyme, together with a metal coordination bond with the metal ions, thus supporting its micromolar inhibition of La ARG …”
Section: Arginasementioning
confidence: 99%
“…Cinnamide, also known as cinnamamide or cinnamic acid amide, has a wide distribution and application in the fields of natural products and medicinal chemistry with a wide range of pharmacological activities. , It is important to note that cinnamide-based derivatives could be used as a promising framework for the development of anticancer agents . Over the past few years, the anticancer activities of numerous cinnamide derivatives have been increasingly reported to show potent anticancer activities on targets such as mitochondria, tubulin polymerization, and so on. , Cinnamide is also frequently used as a potential pharmacological active fragment in the design of EGFR tyrosine kinase inhibitors .…”
Section: Introductionmentioning
confidence: 99%